The Systematic Reconnaissance Flight (SRF) as a tool in assessing the ecological impact of a rural development programme in an extensive area of the Lowveld of South Africa - Peel, Michael John Stephen; Stalmans, Marc (African journal of ecology, 1999)
Land use cover and the current ecological condition of the natural resources of a 71,300 ha area were assessed quantitatively and qualitatively. The Systematic Reconnaissance Flight (SRF) was used to achieve the above within severe time constraints set by the terms of reference for the project. North–south grid lines, spaced 1 and 2 km apart, were flown using a helicopter. Changes in land use classes along flight transects were documented using a Global Positioning System. The co‐ordinates were transformed within a Geographic Information System into land cover values. The SRF with sampling intensities ranging from 5.13 to 9.89% yielded a difference of only 0.2% between the estimated cover of sugar cane compared to the known area under sugar cane. The other land cover classes were considered adequately quantified. The qualitative assessment shows the natural resources to be under severe strain, in particular within the riparian zone. Recommendations as to future agricultural expansion are made. The SRF was highly cost‐effective in achieving the stated objectives of the project. Résumé On a évalué quantitativement et qualitativement la couverture du territoire et les conditions écologiques actuelles des ressources naturelles d’une zone de 71300 ha. On a utilisé le Vol de Reconnaissance Systématique (VRS) pour terminer ce projet dans les délais très stricts imposés par ses termes de références. Des tracés nord‐sud du réseau, espacés de 1 et 2 km l’un de l’autre, ont été parcourus en hélicoptère. Les changements de classe d’utilisation de territoire observés le long des transects survolés étaient notés en utilisant un Global Positioning System. Les coordonnées étaient transformées par un Système d’Information Géographique en valeurs de couverture du territoire. Le VRS, dont les intensités d’échantillonnage allaient de 5,13 à 9,89%, a présenté une différence de 0,2% seulement entre l’estimation de la couverture de la cane à sucre par rapport à la surface connue couverte de cane à sucre. On a considéré que les autres classes de couverture du territoire étaient quantifiées correctement. L’évaluation qualitative montre que les ressources naturelles subissent une pression sévère, particulièrement dans la zone riveraine. On fait des recommandations pour les expansions agricoles à venir. Le VRS s’est révélé très rentable pour la réalisation des objectifs du projet.